2021
DOI: 10.1556/1326.2020.00828
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-UV method for quantification of favipiravir in pharmaceutical formulations

Abstract: Favipiravir (FVP), a pyrazine analog, has shown antiviral activity against a wide variety of viruses. It is considered to be worth further investigation as a potential candidate drug for COVID-19. It is not officially available in any pharmacopoeia. A rapid, simple, precise, accurate, and isocratic high performance liquid chromatography (HPLC) method has been developed for routine quality control of favipiravir in pharmaceutical formulations. Separation was carried out by C18 column. The mobile phase was a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 10 publications
0
81
0
1
Order By: Relevance
“…As it was mentioned earlier, a survey of the literature revealed that there are only two studies for the quantitative determination of favipiravir. In the first attempt, it was reported the use of high performance liquid chromatography with UV detection [ 17 ]. LOD value equaled to 1.20 mg mL ‒1 has been estimated in a mobile phase consisting potassium dihydrogen phosphate 50 mM (pH 2.3) and acetonitrile (90:10, v/v).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was mentioned earlier, a survey of the literature revealed that there are only two studies for the quantitative determination of favipiravir. In the first attempt, it was reported the use of high performance liquid chromatography with UV detection [ 17 ]. LOD value equaled to 1.20 mg mL ‒1 has been estimated in a mobile phase consisting potassium dihydrogen phosphate 50 mM (pH 2.3) and acetonitrile (90:10, v/v).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from these requirements, such studies in biological matrices will assist in the development of new drugs [ 16 ]. Survey of the literature revealed that only two studies have been made on the quantification of favipiravir by using high performance liquid chromatography coupled with ultraviolet (UV) detection [ 17 ], and spectrofluorimetric method [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is being used now as a possible treatment for COVID-19 infection (NCT, 2020;Pilkington et al, 2020;Radhakrishnan et al, 2020).Searching the literature there is no method for determination of FAV in human plasma. Only one HPLC method was described for quantification in pharmaceutical formulations (Bulduk, 2021). The aim of this work was to develop a sensitive, rapid and reproducible method for estimation of FAV in human plasma to allow high output analysis, which is required for a pharmacokinetic and bioequivalence study.…”
Section: Introductionmentioning
confidence: 99%
“…The run time was 15 min under these chromatographic conditions. Excellent linear relationship between peak area and Favipiravir concentration in the range of 10-100mg/ml has been observed [6].…”
Section: Introductionmentioning
confidence: 73%